2011
DOI: 10.1097/jom.0b013e31820c3f87
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Work Schedules, Home, and Work Demands on Self-Reported Sleep in Registered Nurses

Abstract: Current scheduling practices and high work demands negatively impact nurses' sleep and may be partially explained by exposure to work demands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 35 publications
1
70
2
2
Order By: Relevance
“…One field study showed that nurses reported significantly lower sleep quality after quick returns of 10.0 hours from evening to A c c e p t e d M a n u s c r i p t morning shifts in an 8-hour system, compared to those with longer changeovers in a 12-hour system (Costa et al 2014). One cross-sectional study showed that quick returns of 10.0 hours were positively associated with more frequent reports of inadequate and restless sleep among nurses (Geiger-Brown, Trinkoff, and Rogers 2011). Three survey studies support a positive association between quick returns and shift work disorder (Eldevik et al 2013), of which one was a longitudinal study .…”
Section: Sleep Duration and Disturbed Sleepmentioning
confidence: 94%
See 2 more Smart Citations
“…One field study showed that nurses reported significantly lower sleep quality after quick returns of 10.0 hours from evening to A c c e p t e d M a n u s c r i p t morning shifts in an 8-hour system, compared to those with longer changeovers in a 12-hour system (Costa et al 2014). One cross-sectional study showed that quick returns of 10.0 hours were positively associated with more frequent reports of inadequate and restless sleep among nurses (Geiger-Brown, Trinkoff, and Rogers 2011). Three survey studies support a positive association between quick returns and shift work disorder (Eldevik et al 2013), of which one was a longitudinal study .…”
Section: Sleep Duration and Disturbed Sleepmentioning
confidence: 94%
“…There is also a predominance of female subjects due to the large survey studies on health personnel (Geiger-Brown, Trinkoff, andRogers 2011, Flo et al 2014). This may reflect a bias within the field since research results are not always generalizable between the sexes (Holdcroft 2007).…”
Section: Limitations and Further Directionmentioning
confidence: 96%
See 1 more Smart Citation
“…While there are several cross-sectional 11 studies (Akerstedt et al, 2002;Geiger-Brown, Trinkoff, & Rogers, 2011), and a few longitudinal studies (Burgard & Ailshire, 2009;de Lange, Kompier, Taris, Geurts, Beckers, Houtman, et al, 2009) demonstrating an association between work-related stress and sleep, the mechanism/s by which occupational stress influences sleep remain uncertain. However, the sleep literature agrees that one of the factors thought to interfere with sleep is perseverative thinking (e.g., rumination, worry), with self-reported sleep disturbance showing a strong association with work-related worries and rumination (Akerstedt et al, 2002;Cropley et al, 2006).…”
Section: Work-related Rumination and Recovery From Workmentioning
confidence: 99%
“…The Institute of Medicine (IOM) called for nurse work environment change to meet these needs [9]. Extended work shift hours expose nurses to increased workplace stressors compared to regularly scheduled shifts [10] and an increase in accidents, injuries, and other incidents are associated with long work hours [10][11][12][13][14][15]. Nurses work 12-hour shifts to provide continuous 24-hour inpatient care creating sleep deprivation and higher stress demands.…”
Section: Literature Reviewmentioning
confidence: 99%